Tastes like music : 17 quirks of the brain and body - Birmingham, Maria (Owlkids, 2014)
Humans may all look pretty much the same on the outside, but some people have unique conditions and amazing abilities! Whether it's having no fingerprints at all (adermatoglyphia), hearing music every time you taste chocolate (synesthesia), or being able to see one hundred million colors (tetrachromacy), some conditions bring our understanding of the human body to another level entirely.